1968
DOI: 10.1002/hlca.19680510522
|View full text |Cite
|
Sign up to set email alerts
|

Optische Rotationsdispersion von Indolinalkaloiden mit Ketogruppen

Abstract: l) Fig. 1 ist aus der Arbeit [3] zum leichteren Verstandnis reproduziert. H~~v a~x c . 4 CHIMICA Xc.r.4 ~ \-ohmen 51, Fasciculus 5 (1968) 1169

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1968
1968
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…One oxygenated methine group (δ C 73.4) was assigned to C-22 from the HMBC cross-peaks between H-22 (δ H 4.50, dd, J = 9.5, 1.5 Hz) and C-17 (δ C 38.7), C-5 (δ C 48.8), and C-16 (δ C 80.1) (Figure ). Thus, C-6 and C-16 were linked through C-22, a characteristic of a kopsine-type alkaloid, similar to demethoxycarbonylkopsin ( 10 ) . Comparing the NMR data with those of compound 10 showed that the carbonyl group in compound 10 (δ C 212.0) was replaced by an oxygenated methine group (δ H 4.50, δ C 73.4) in 1 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One oxygenated methine group (δ C 73.4) was assigned to C-22 from the HMBC cross-peaks between H-22 (δ H 4.50, dd, J = 9.5, 1.5 Hz) and C-17 (δ C 38.7), C-5 (δ C 48.8), and C-16 (δ C 80.1) (Figure ). Thus, C-6 and C-16 were linked through C-22, a characteristic of a kopsine-type alkaloid, similar to demethoxycarbonylkopsin ( 10 ) . Comparing the NMR data with those of compound 10 showed that the carbonyl group in compound 10 (δ C 212.0) was replaced by an oxygenated methine group (δ H 4.50, δ C 73.4) in 1 .…”
Section: Resultsmentioning
confidence: 97%
“…Thus, C-6 and C-16 were linked through C-22, a characteristic of a kopsine-type alkaloid, similar to demethoxycarbonylkopsin (10). 18 Comparing the NMR data with those of compound 10 showed that the carbonyl group in compound 10 (δ C 212.0) was replaced by an oxygenated methine group (δ H 4.50, δ C 73.4) in 1. The 2D structure of compound 1 was defined by the key HMBC connectivities shown in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21) were isolated from K. officinalis. Additionally, Kopsinine methochloride (237), demethoxycarbonylkopsin (238) [111], methyl chanofruticosinate (239), methyl 11,12-methylenedioxychanofruticosinate (240) [94], methyl 12-methoxychanofruticosi nate (241), methyl 11,12-methylenedioxy-N 1 -decarbomethoxychanofruticosinate (242) [112], kopsininic acid (243), and (−)-11,12-methylenedioxykopsinaline (244) [98] were identified from the same species. Furthermore, (−)-N-methoxycarbonyl-11,12-methylenedioxykopsinaline (245) [98], (−)-N-methoxycarbonyl-12-methoxykopsinaline (246), N-carbomethoxy-11-hyd roxy-12-methoxykopsinaline (247) [113], kopsinoline (248) [114], (−)-12-methoxykopsinaline (249) [98], 11,12-methylenedioxykopsinaline N(4)-oxide (250) [87], kopsinine B (251) [115], rhazinilam (252) [66], and pleiocarpamine methochloride (253) [116] were all isolated from the twigs and leaves of chines K. officinalis.…”
Section: Kopsiamentioning
confidence: 99%
“…Daniit kann fur Scandin (11) die in der Kaumforniel 11 r angegebene relativc K o nfiguration als gesichert gelten. Es ist nocli zu entscheiden, oh das Meluscin (1) oder das Epiineloscin (10) bezuglicli dei-Verknupfung der Kinge R un.3 C deni Scandin ( In den Arbeitskreisen uin KLYKE und SCHMID rj4] [5] ist geezigt worden, dass N(Lacetylierte Alkaloid-de; Aspidtsperniinund Strychnin-Typs, der-n nichta-amatiscli.~ Doppelbindungm aushydriert sind, se'ir ahnliche 0RD.-Kurven liefern, wenn sie der gleichen sterischen Reihe hezuglicli des Spirozentruins C-12 bzw. C-3 angelloren.…”
Section: Is00unclassified